2016
DOI: 10.1007/s11605-015-3025-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Peptic Ulcer Disease in sub-Saharan Africa: Systematic Review of Published Data

Abstract: Peptic ulcer disease remains a significant indication for surgery in sub-Saharan Africa. Recognizing the continued role of surgery for peptic ulcer disease in sub-Saharan Africa is important for strengthening surgical training programs and optimizing allocation of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…2,3 Other investigators have also noted increased risk of death with an increasing interval between perforation and initiation of treatment. [20][21][22][23]38 The same has not been observed in this study. The delay in presentation did not have a significant impact on mortality.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…2,3 Other investigators have also noted increased risk of death with an increasing interval between perforation and initiation of treatment. [20][21][22][23]38 The same has not been observed in this study. The delay in presentation did not have a significant impact on mortality.…”
Section: Discussionsupporting
confidence: 61%
“…Rickard et al in a review of surgery for complications of peptic ulcer reported a 60% vagotomy rate from subsaharan Africa. 23 Seow et al have found a gastric resection rate of 1 in 10 in a series of 599 patients of PPU operated over a period of 8 years. 29 Agaba reported a 2% definite anti-ulcer procedure in a decade long period with 98% patch closure.…”
Section: Discussionmentioning
confidence: 97%
“…Patients, who underwent surgery for PUD in Sub-Saharan Africa, indicated that 86% suffered from duodenal ulcers while the rest 14% had gastric ulcer. e major complications like perforation (35%), bleeding (7%), obstruction (30%), and chronic case (28%) were indicated for surgery, and the overall fatality rate was found to be 5.7% [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ideal treatment option for patients with peptic ulcer perforation is primary suturation and irrigation of peritoneal cavity in an emergency manner. [3] However, it is controversial that whether laparoscopic approach or conventional open surgery should to be choose. Although laparoscopic surgery has great advantages such as short hospital stay, less level of pain, better cosmetic results, it requires a certain learning curve and experiences to gain afformentioned advantages.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Peptic ulcer perforation is a condition that requires immediate surgical intervention and open or laparoscopic surgery may be preferred. [1,3] As is known, most elective open surgeries have more intraoperative blood loss than laparoscopic surgery, more postoperative hospital stay and more postoperative pain. [4][5][6] Studies have shown that emergency laparotomy is associated with 5% mortality, 20% morbidity and 3% long term bowel obstruction.…”
Section: Introductionmentioning
confidence: 99%